THE ANALYSIS OF PEDAGOGICAL COMPETENCE OF PRE-SERVICE TEACHERS AT UNIVERSITAS NEGERI MAKASSAR 1ST BATCH - Nur Ahdaniyah MZ; Sitti Nurjannah; Jusmaniar N (ADHILINGUA: Journal of Language Education, Lilnguistics and Literature, 2024)
The purpose of this study is to evaluate Universitas Negeri Makassar pre-service teachers' pedagogical competence. This study's methodology entails qualitative examination of information gathered by observation, interviews, and reflection. The research sample consisted of 5 pre-service teacher program students randomly selected from several departments at Universitas Negeri Makassar. The results of the study are: 1) Pre-service teachers have a strong Understanding the insights and foundations of education, prior to service Teachers are aware of the fundamentals of education and the philosophy and policy underlying their teaching practices. 2) Understanding students and teachers demonstrates a good comprehension of students' characteristics and needs, including physical, emotional, and social development. They can identify the student's unique needs and respond well to them. 3) Pre-service teachers prepare lesson plans and syllabus by the applicable curriculum. 4) Pre-service teachers produce structured and well-planned learning, including setting learning objectives and selecting appropriate methods. 5) pre-service teachers can carry out interactive and educational learning with a dialogical approach that actively incorporates pupils into the process of learning. 6) Pre-service teachers have basic skills in using learning technology. 7) Pre-service teachers use various evaluation tools. However, formative assessments are often used. 8) Pre-service teachers have successfully designed activities to support students' potential and interests, including integrating extracurricular activities with the curriculum.